Job applications and labour market flows - Serdar Birinci; Kurt See; Shu Lin Wee (Bank of Canada, 2021)
Job applications have risen over time, yet job-finding rates have remained unchanged. Meanwhile, job separations have declined. We argue that an increase in the number of applications raises the probability of finding a good match rather than the probability of finding a job. Using a search model with multiple applications and costly information, we show that when applications increase, firms invest in identifying good matches, thereby reducing separations. Concurrently, increased congestion and selectivity over which offer to accept temper increases in job-finding rates. Our framework contains testable implications for changes in offers, acceptances, reservation wages, applicants per vacancy, and tenure, factors that enable us to generate the trends in unemployment flows.
Keywords: E24; J63; J64; 330; Labour markets; Productivity